PEMANFAATAN SOFTWARE CUBASE 5 SEBAGAI MEDIA PEMBUATAN MUSIK DIGITAL BAGI MAHASISWA SENI MUSIK PRODI PENDIDIKAN SENI PERTUNJUKAN UNIVERSITAS TANJUNGPURA - Geovani Risa Krisanta; Imam Ghozali; Yudhistira Oscar Olendo (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the use of features in Cubase 5 software as a medium for making digital music. Describes how to optimize the use of features in Cubase 5 software to support creativity in digital music creation for Music Arts Students in the Performing Arts Education Study Program, Tanjungpura University. Describes the benefits of Cubase 5 software for Music Arts Students in the Performing Arts Education Study Program, Tanjungpura University. This study uses descriptive methods in the form of qualitative and qualitative approaches. The source of data in this study is Rosidin. Wildan Naraya Dirgantara. Ranma Yustistio. Data collection techniques in the form of observation, interviews and literature study. The technique of testing the validity of the data used is source triangulation. The result of this study is that the Cubase 5 software has benefits in its use for Music Arts Students of the Performing Arts Education Study Program, Tanjungpura University related to subjects that require creativity such as arrangement, basic composition, advanced composition and dance accompaniment music for dance students.Keywords: Utilization, Cubase 5, Software